Mechanism of New Particle Formation and Growth as well as Environmental Effects under Complex Air Pollution in China - Min* Hu; Shang, D. J.; Guo, S.; ZJ Wu (Acta Chimica Sinica, 2016)
New particle formation (NPF) and its subsequent growth plays a key role in air quality and climate change at regional and global scales. Especially under complex air pollution in China, nucleation and growth can be highly efficient, claimed to be a main source of cloud condensation nuclei (CCN) and an important cause of secondary aerosol pollution. Currently, the mechanism of particle formation and growth as well as its environmental effects are still poorly understood. Thereby, fully understanding of the atmospheric nucleation and subsequent growth still presents a big challenge to atmospheric chemistry researches. This study reviews the current results from studies on mechanisms and environmental effects of atmospheric nucleation and growth. We summarize that traditional nucleation theories such as binary nucleation of H2SO4-H2O, ternary nucleation of H2SO4-NH3-H2O, ion-induced nucleation are not capable in explaining new particle formation under complex air pollution, while newly proposed mechanisms such as organic acids and amine induced nucleation were not verified because of technique limitation. We propose that the future researches should focus on identifying the key chemical precursor response for driving nucleation and initial and subsequent growth, and understand the physical and chemical processing of new particle formation and growth. In particularly, application and development of novel techniques, such as APi-TOF-CIMS, PSM, Nano-HTDMA in new particle formation study is very important. Also, future researches should establish whole process tracking on new particle formation, from precursor, nucleation, growth till the environmental effects, by integrating field observation, chamber simulation, and modelling. Currently, the mechanism of highly efficient nucleation and rapid growth taking place under complex air pollution in China is urgently needed to be in-depth studied in order to improve our understanding of regional haze formation. This could be helpful to understand the similarity and difference in the nucleation mechanism between clean and polluted atmospheric environments.
Keywords: atmospheric nanoparticle growth; cloud condensation nuclei; complex air pollution; environmental impact; formation events; long-term; new particle formation; nucleation; number size distributions; particle growth; river delta; secondary organic aerosol; sulfuric-acid concentration; transformation mechanism; urban atmosphere